Alkohol ist ein gefährliches Produkt - John, Ulrich (DMW - Deutsche Medizinische Wochenschrift, 2017)
Alcohol is a hazardous product. Its consumption depends on the society’s drinking norms. These are set by advertising industries on the one hand, and forces of public health and medical services on the other hand. Germany is one of the countries with high alcohol consumption. According to epidemiological evidence, alcohol-attributable diseases include more than 200 diagnostic entities. Medical practitioners may help to reduce alcohol consumption. Data revealed that brief intervention, including computer-generated feedback in medical practice, is efficient in reducing consumption. It relieves the physician of counseling responsibilities.
Keywords: Alkohol-attributable Krankheit; soziale Norm; Suchtmittel; Beratung; Feedback